Identification of potential novel hosts and the risk of infection with lymphocytic choriomeningitis virus in humans in Gabon, Central Africa - Yuri Ushijima; Haruka Abe; Takehiro Ozeki; Georgelin N. Ondo; Marien J.V.M. Mbadinga; Rodrigue Bikangui; Chimène Nze-Nkogue; Etienne F. Akomo-Okoue; Ghislain W.E. Ella; Lilian B.M. Koumba; Branly C.B.B. Nso; Rodrigue Mintsa-Nguema; et al. (International Journal of Infectious Diseases, 2021)
Objectives: Lymphocytic choriomeningitis virus (LCMV), a human pathogenic arenavirus, is distributed worldwide. However, no human cases have been reported in Africa. This study aimed to investigate the current situation and potential risks of LCMV infection in Gabon, Central Africa. Methods: A total of 492 human samples were screened to detect LCMV genome RNA and anti-LCMV IgG antibodies using reverse transcription-quantitative PCR and enzyme-linked immunosorbent assay (ELISA), respectively. ELISA-positive samples were further examined using a neutralization assay. Viral RNAs and antibodies were also analyzed in 326 animal samples, including rodents, shrews, and bushmeat. Results: While no LCMV RNA was detected in human samples, the overall seroprevalence was 21.5% and was significantly higher in male and adult populations. The neutralization assay identified seven samples with neutralizing activity. LCMV RNA was detected in one species of rodent (Lophuromys sikapusi) and a porcupine, and anti-LCMV IgG antibodies were detected in four rodents and three shrews. Conclusions: This study determined for the first time the seroprevalence of LCMV in Gabon, and revealed that local rodents, shrews, and porcupines in areas surrounding semi-urban cities posed an infection risk. Hence, LCMV infection should be considered a significant public health concern in Africa.